Approach for statistical analysis of oxide- and sulfate-induced hot corrosion of advanced alloys. (February 2023) - Chikhalikar, Atharva S.; Godbole, Eeshani P.; Poerschke, David L.
Abstract: This work develops an automated image and statistical analysis protocol to characterize and compare the effect of three deposits on the accelerated non-uniform degradation of a model alloy (FeCrAlY) at 1025 °C in dry air. Compared to the sample tested without a deposit, the Ca-containing mixed oxide deposit increased the frequency of oxide intrusions into the alloy. The CaSO4 and Ca-containing mixed sulfate deposits reacted with the thermally grown oxide (TGO) to form less-protective calcium aluminates and increased the roughness of the alloy-TGO interface. However, the mixed sulfate deposit melted and spread, increasing the uniformity of the attack. Graphical Abstract: ga1 Highlights: Image analysis protocol was developed to quantify features of alloy degradation. TGO thickness and interface roughness depended on the deposit composition. A solid, mixed oxide deposit slightly increased the frequency of oxide intrusions. Reactions with solid CaSO4 to form less-protective Ca-aluminates varied significantly. A molten mixed sulfate deposit caused more uniform Ca-aluminate formation.